Psikoedukasi Pencegahan Kekerasan Seksual Di SMA Tarakanita Citra Raya - HW, Astri Anggraini; Imanuel, Dastin; Rasyid, Damar; Jenica, Bunga; Audrey Orlanthia Alveria (Universitas Negeri Padang, 2025)
Sexual violence is a serious issue that has a broad impact on the physical, psychological, and social well-being of adolescents. This study aims to evaluate the effectiveness of a psychoeducational seminar in increasing students' awareness of sexual violence prevention at Tarakanita Citra Raya High School. The method used was a descriptive quantitative approach with a pre-test and post-test design without a control group. A total of 162 students participated and completed the